The Impact of Gamification on Student Learning Processes in Technical Education: A Qualitative Exploration in Blended Learning - Suarmika, Putu Eka; Febriani (Generate Digital Publishing, 2024)
Objective: This research aims to assess the impact of gamification in engineering education in a blended learning environment, focusing on increasing students' motivation, engagement, understanding of technical concepts, and development of social skills and soft skills. The research also explores the role of technology in supporting gamification and identifies challenges in its implementation. Research Design & Methods: This research uses a qualitative approach based on literature analysis and case studies of previous studies. Gamification elements, such as points, leaderboards, challenges and rewards, integrated into a technology-supported blended learning environment such as an ERP simulator and interactive platform. Data was analysed to evaluate the impact of gamification on students' learning outcomes and social skills development. Findings: This research uses a qualitative approach with literature analysis and case studies. Gamification elements such as points, leaderboards, challenges and rewards are integrated in technology-supported blended learning such as ERP simulators and interactive platforms to evaluate their impact on learning outcomes. Implications & Recommendations: Implementing successful gamification in engineering education requires adaptive and flexible design to ensure game elements not only increase motivation, but also remain focused on deep academic goals. It is recommended that educators and learning developers pay attention to the different learning styles of students and avoid overusing competitive elements. Contribution & Value Added: This research shows how gamification supports engineering learning in blended learning, emphasising the important role of technology and the challenges of its implementation. The findings offer adaptive design solutions to improve learning effectiveness.